Urban Identitites and Diversities: A Key to the Renaissance of the City? - Bitušíková, Alexandra (Lidé města, 2007)
This paper looks at factors of urban identity forming in a contemporary city. It studies diversity as one of the characteristics of the city and its relation to identity as the other side of diversity. It explores urban strategies that focus on the regeneration of historic city centres and revitalisation of urban life and urban identities as well as on attracting visitors and investors to the city. This emphasis on cultural planning is an important part of urban development strategies that aim at the support and growth of local economies. This paper presents a case study of the middle-size city of Banska Bystrica (Central Slovakia). It identifies and analyses six factors that contribute to urban identity construction in the city and examines hetero-images – reflections of the image of the city in the minds and memories of visitors. In the final part the paper focuses on studying the local government approach to revitalisation of urban life in Banska Bystrica.